Complete C4-C5 Dislocation Secondary to Shallow Water Diving in a Child: A Case-Based Update - Matos, Luís Eduardo Oliveira; Figueiredo, Gabriel Sá; Monteiro, Matheus Brasil Câmara; Esmeraldo, Mateus Aragão; Ponte, Keven Ferreira da; Cristino-Filho, Gerardo; Leal, Paulo Roberto Lacerda (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2023)
Introduction Pediatric spinal cord injury (PSCI) is rare, especially secondary to shallow water diving, with only a few cases recorded in the literature. Due to the low standardization in the diagnosis and treatment of this condition, each of these cases requires a personalized approach.Case Description A 10-year-old female patient presented with tetraparesis and C5 sensory level secondary to spinal trauma due to shallow water diving. Computed tomography (CT) revealed complete C4-C5 dislocation, which led to a neurosurgical approach preceded by an intraoperative manual maneuver to reduce the dislocation. Following complete surgical reduction of the dislocation, the patient presented immediate significant neurological improvement.Conclusion Children need to be warned about diving, as SCI due to shallow water diving has a poor neurological outcome. Despite that, early diagnosis, stabilization, and surgical approach can lead to immediate significant neurological improvement. Considering the peculiarities of pediatric patients and the existence of varying care techniques in the literature, more studies comparing surgical and nonsurgical outcomes are fundamental.
Keywords: pediatric spinal cord injury; shallow water diving; cervical dislocation; spinal trauma management